2006
DOI: 10.1021/jp057030e
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Analytical Studies of the Electrical Conductivity of a Concentrated Colloidal Suspension

Abstract: In the past few years, different models and analytical approximations have been developed facing the problem of the electrical conductivity of a concentrated colloidal suspension, according to the cell-model concept. Most of them make use of the Kuwabara cell model to account for hydrodynamic particle-particle interactions, but they differ in the choice of electrostatic boundary conditions at the outer surface of the cell. Most analytical and numerical studies have been developed using two different sets of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…This condition is also consistent with the Maxwell limit for a suspension of uncharged spheres (Maxwell, 1873), where the conductivity of the solution becomes independent of the zeta potential (Carrique et al, 2001;Cuquejo et al, 2006;Jeffrey, 1973;McKenzie et al, 1978;Ohshima, 1999;Sangani and Acrivos, 1983). A detailed description of this phenomenon is provided in Hunter (2001).…”
Section: Electrical Conductivitysupporting
confidence: 67%
See 3 more Smart Citations
“…This condition is also consistent with the Maxwell limit for a suspension of uncharged spheres (Maxwell, 1873), where the conductivity of the solution becomes independent of the zeta potential (Carrique et al, 2001;Cuquejo et al, 2006;Jeffrey, 1973;McKenzie et al, 1978;Ohshima, 1999;Sangani and Acrivos, 1983). A detailed description of this phenomenon is provided in Hunter (2001).…”
Section: Electrical Conductivitysupporting
confidence: 67%
“…These models primary use the Kuwabara's cell model but differ by the electrostatic boundary conditions at the outer surface of the cell. Cuquejo et al (2006) recently reported an analytical model that matches well with experimental data for wide range of f and /, but only valid in the limit of thin EDL (large ja). To our knowledge there are still no existing models that accurately predict the conductivity modification of a suspension for arbitrary values of the electrokinetic radius ja.…”
Section: Electrical Conductivitymentioning
confidence: 84%
See 2 more Smart Citations
“…Actually, to describe the case of charged nanoparticles, it is difficult to choose the right conceptual framework: Are suspensions of charged nanoparticles still electrolyte solutions, or should they be viewed through the lens of colloidal theories ? Theories of colloidal conductivity are adapted to the description of suspensions in which the length scales relative to the colloid and the ions of the supporting electrolyte are very different (see for instance [32,33] for static, and [34,35] for frequency dependent measurements). For dispersions containing colloidal particles with a nanometric size -a radius smaller than 10 nm-, such theories do not seem to be relevant.…”
Section: Introductionmentioning
confidence: 99%